Life cycle assessment of cement-based products: critical review and future perspectives - Lucena, Gabriel; Nascimento, Maria Luiza Araujo do; Pinho, Giusilene Costa de Souza; Mattos, Flávio (Brazilian Journal of Production Engineering, 2026)
The construction industry has a significant environmental impact, accounting for a considerable portion of global raw material consumption and greenhouse gas emissions, a situation exacerbated by the intensive use of cement and the energy required for its production. These factors have driven studies aimed at quantifying such impacts, establishing Life Cycle Assessment (LCA) as a fundamental technical tool for this measurement. In this regard, this study presents a systematic review of the literature on LCA applied to cementitious products, conducted in accordance with the PRISMA protocol. The research covered the Scopus and Web of Science databases (2014–2025). After applying eligibility criteria based on the guidelines of ISO 14040 and 14044, and discarding superficies approaches, the final portfolio consisted of 69 articles (3 reviews and 66 original studies). The results of this study indicate a predominance of research on concrete (84%), and the main category studied was “global warming potential” (83%). However, critical gaps were identified: 44% of the studies omitted impact methods, and 9% did not define the system boundaries. Finally, it is evident that although LCA is a well-established tool, the field requires greater methodological standardization, the inclusion of socioeconomic indicators, and more in-depth sensitivity analyses.